In-vitro assessment and characterization of anticancer, antibacterial, and antioxidant activity of diatom-derived metabolites - Raya Bhattacharjya; Rashi Tyagi; Sangita Dey; Ankita Dutta; Anoop Kumar; Mostafa M. El-Sheekh; Subha Rastogi; Nutan Kaushik; Archana Tiwari (Scientific Reports)
Abstract Microalgae are known to produce a spectrum of highly valuable metabolites with substantial nutritional content and pharmacogenetic properties. To explore the antioxidant, antibacterial, as well as anticancer activity of five such microalgal strains isolated from the Indian subcontinent, solvent-based extracts were prepared using methanol:chloroform (S1, v/v) and ethyl acetate (S2). The DPPH and ABTS radical scavenging assays revealed maximum inhibition (65.42% and 69.73%) by S1 extract of Cylindrotheca sp. (D3) and 72.08% and 77.43% by S2 extracts of Chaetoceros sp. (D1), respectively. Both S1 and S2 extract of Cylindrotheca sp. showed maximum zone of inhibition (24 ± 0.4 mm) against Aeromonas sp. and Streptococcus pneumoniae. Further, in-vitro anticancer assessment was also done against renal adenocarcinoma (ACHN), lung carcinoma (A549), and ovarian carcinoma (SK-OV3) cell lines. Highest cytotoxicity was observed when SK-OV3 (63.3%) and A549 (53.6% ) cells were treated with 250 µg mL−1 of S1D1 extract. Major bioactive constituents identified by GC-MS estimation included palmitic, heptadecaenoic, octadecanoic, linoleic, eicosapentaenoic acid, 2,4-Di tertbutyl phenol, and Desulphosinigrin amongst others. Thus, this study provides an insightful and holistic overview on microalgal bioactivities and their potential as natural therapeutic resources targeting different human pathogenic disorders and diseases.